Physicochemical effects in aging aqueous Laponite suspensions - Shahin, A (Langmuir : the ACS journal of surfaces and colloids, 2012)
We study aging behavior of an aqueous suspension of Laponite as a function of concentration of Laponite, concentration of salt, time elapsed since preparation of suspension (idle time), and temperature by carrying extensive rheological and conductivity experiments. We observe that temporal evolution of elastic moduli, which describes structural build-up and aging, shifts to low times for experiments carried out for higher concentration of Laponite, higher concentration of salt, greater temperature, and longer idle time while preserving the curvature of evolution in the solid regime (elastic modulus greater than viscous modulus). Consequently appropriate shifting of evolution of elastic modulus in the solid regime leads to aging time-idle time-salt concentration-Laponite concentration-temperature superposition. The existence of such a superposition suggests the generic nature of microstructure buildup irrespective of mentioned variables in the explored range. The behavior of shift factors needed to obtain the superposition indicate that the energy barrier associated with structural buildup decreases with an increase in idle time and temperature and decreases linearly with an increase in concentration of Laponite and that of salt. The conductivity experiments show that ionic conductivity of the suspension increases with increasing Laponite concentration, salt concentration, temperature, and very importantly the idle time. We also analyze the interparticle interactions using DLVO theory that suggests an increase in idle time, temperature, and salt concentration increases the height of the repulsive energy barrier while it decreases the width of the same when particles approach each other in a parallel fashion. However when particles approach each other in a perpendicular fashion, owing to dissimilar charges on edge and face, the energy barrier for the attractive interaction is expected to decrease with an increase in idle time, temperature, and salt concentration. Analysis of rheological and conductivity experiments suggests a strong influence of attractive interactions on the low energy structures in an aqueous suspension of Laponite